Experimental Study on the Heterogeneity of Mechanical Properties of Friction Stir Welded Joints with the Digital Image Correlation Method - Li, H.; Dai, Q.-L.; Shi, Q.-Y. (Проблемы прочности, 2015)
The heterogeneity of mechanical properties of friction stir welded 6082 aluminum butt joints were analyzed with the digital of image correlation (DIC) method. The DIC method provides instantaneous full-field strain distribution data for weld surfaces. Visualized strain field images and local stress–strain curves of weld subzones were derived from these data. The heterogeneity was evaluated by assessing strain concentrations in the strain field images and comparing the constitutive parameters of weld subzones. Furthermore, by comparing these variables of different surfaces of the weld, the potential impact of the mutual constraint between subzone materials on the heterogeneity level was analyzed..